Analysis of Sports Injuries in Garuda Acalapati Basketball Club Athletes - Kautsar Rafiqih Tenggara; Junaidi Junaidi; Ela Yuliana; Heni Widyaningsih; Sri Indah; Yasep Setiakarnawijaya (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study was conducted to determine the percentage of athletes who have been injured, are injured, and know the body parts that have been injured, the nature of the injury, the time of injury, the type of injury, the degree of injury, the cause of the injury, as well as the handling of the injury. The research method used is descriptive quantitative with surveys as the research instrument. The research population was basketball athletes of the Garuda Acalapati Club. The criteria used by researchers are as follows: 1) Active athletes at Garuda Acalapati basketball club,2) Aged 16-18 years. Based on the criteria, the sample who met the criteria were 49 athletes. The results of data processing showed that 4 athletes have never experienced injury and 45 athletes have experienced injury. The most common type of injury in athletes was in the ankle 49%. Based on the type of acute injury 63%. Time of injury during training by 73%. Based on the type of injury was an injury to the skin (abrasions, wounds, open, bruises) by 63%. Based on the degree of injury was minor injury by 76%. Based on the cause of injury External Violence (cause was from outside of the body) collisions with opponents by 63%. Handling of injuries was self-handling by 73%. Thus the a need for special handling or prevention programs for athletes conducted by the coaching team because there were still many athletes who experienced injuries.